Effect of diabetes mellitus on physical function in patients with osteoarthritis: a cross-sectional observational study - Que, Zhiqiang; Xu, Wenbin; Xiao, Keyi; Chen, Cunbin; Shu, Jianghao; Huang, Yuxuan; Chen, Dingqiang; Rui, Gang (Frontiers in Endocrinology, 2025)
BackgroundOsteoarthritis (OA) is a common chronic disease among the elderly, causing pain, functional limitations, and a decline in quality of life. Diabetes mellitus (DM), a prevalent metabolic disorder, has been proven to have an association with OA. However, the specific impact of DM on the physical function of OA patients remains lack of in-depth exploration. This study aims to investigate whether OA patients with DM (DMOA) experience more severe physical function limitations.MethodThe study utilized National Health and Nutrition Examination Survey (NHANES) data from 1999-2018. Logistic regression models were used to analyze the association between DMOA and physical function limitations. Stratified analysis was applied to assess the stability of these results.ResultsDMOA patients exhibited significantly worse physical function compared to those OA patiants who do not complicated with DM (non-DMOA), especially in high-intensity and frequent joint use activities like walking long distances (OR = 1.870, 95%CI[1.243,2.814], P = 0.003), crouching (OR = 1.417, 95%CI[1.116, 1.799], P = 0.005), and standing for long periods (OR = 1.423,95%CI[1.141,1.774], P = 0.002). Even after adjusting for demographics, socioeconomic and health factors, the association between DMOA and physical function impairment remained significant.ConclusionThis study revealed that the DMOA population has worse physical function than non-DMOA population, especially in high-intensity and frequent joint use activities. Managing DM in OA patients is crucial to improve their physical function and overall quality of life. The impact of DM should be considered in the selection of therapeutic agents and care for OA.